To solve the equation \( 3m + 54 - \frac{3m}{4} = -2 \), we can follow these steps:
- First, we can eliminate the fraction by finding a common denominator. The common denominator for 1 and 4 is 4. We can multiply every term by 4 to eliminate the fraction:
\[ 4(3m) + 4(54) - 4\left(\frac{3m}{4}\right) = 4(-2) \]
This gives us:
\[ 12m + 216 - 3m = -8 \]
- Now, combine like terms:
\[ 12m - 3m + 216 = -8 \]
This simplifies to:
\[ 9m + 216 = -8 \]
- Next, we isolate \( m \) by subtracting 216 from both sides:
\[ 9m = -8 - 216 \]
This simplifies to:
\[ 9m = -224 \]
- Finally, divide both sides by 9 to solve for \( m \):
\[ m = \frac{-224}{9} \]
Thus, the value for \( m \) that makes the equation true is:
\[ \boxed{\frac{-224}{9}} \]